2020
DOI: 10.3389/fpsyg.2020.00990
|View full text |Cite
|
Sign up to set email alerts
|

Natural Categorization: Electrophysiological Responses to Viewing Natural Versus Built Environments

Abstract: Environments are unique in terms of structural composition and evoked human experience. Previous studies suggest that natural compared to built environments may increase positive emotions. Humans in natural environments also demonstrate greater performance on attention-based tasks. Few studies have investigated cortical mechanisms underlying these phenomena or probed these differences from a neural perspective. Using a temporally sensitive electrophysiological approach, we employ an event-related, implicit pas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 71 publications
(102 reference statements)
0
6
0
1
Order By: Relevance
“…A similar result was reported by Foo (2016), who studied people's well‐being in three forests distinguished by their degree of naturalness. Psychophysiological studies have also shown that natural environments are more restorative than built environments (Mahamane et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…A similar result was reported by Foo (2016), who studied people's well‐being in three forests distinguished by their degree of naturalness. Psychophysiological studies have also shown that natural environments are more restorative than built environments (Mahamane et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with ART, a few EEG studies have found evidence of increases in cognitive control activity. For example, brain components such as the error-related negativity (LoTemplio et al 2020), the P300 (Scott et al, under review), and the late positive potential (Mahamane et al 2020) increase in response to nature exposure compared to urban exposure. The reward positivity (McDonnell et al, under review), whose amplitude is inversely related to efficient allocation of attention, decreases in response to nature compared to urban environments.…”
Section: Attention Restoration Theorymentioning
confidence: 99%
“…Adopting an event-related EEG approach with a 14-channel device, Mahamane et al ( 75 ) compared the brain activity on a passive oddball viewing task using scenic images of natural and built environments. Their focus was on the elicited P3 and late positive potential (LPP) responses–neural correlates of categorical differences (greater activation for rare stimuli or updating contexts) and stimulus valence/pleasantness (negative stimuli have greater positive amplitude), respectively.…”
Section: Resultsmentioning
confidence: 99%